Relationship Between Ossicular Chain Erosion and Facial Canal Dehiscence in Chronic Otitis Media Squamous - Kharel, Bijaya; Shreepaili, Ashok; Tripathi, Prashant; Neupane, Yogesh; Gurung, Urmila; Pradhananga, Rabindra B; Rayamajhi, Pabina; Bhattarai, Hari (Journal of Institute of Medicine Nepal, 2020)
Introduction Chronic otitis media squamous is a gradually expanding destructive lesion and leads to complications by eroding the adjacent structures. Facial canal and ossicles are in close proximity in the middle ear space and they share the same pathogenesis of the bony erosion. Ossicular chain erosion found intraoperatively due to cholesteatoma, may suggest the likelihood of facial canal dehiscence. This study was conducted to assess the relationship between ossicular chain erosion and facial canal dehiscence in chronic otitis media squamous.MethodsIt is a retrospective chart review of patients who had mastoidectomy done for chronic otitis media squamous in Tribhuvan University Teaching Hospital from January 2014 to December 2018. The operative findings of facial canal dehiscence were correlated with ossicular chain status.ResultsAmong 158 cases, facial canal dehiscence was seen in 20 (12.7%), of which, 19/20 (95%) had ossicular erosion. Majority (90%) of dehiscence was in the horizontal segment. Incus was the most common ossicle to be eroded. Among the ossicles, stapes erosion was related to the facial canal dehiscence with odds ratio of 3.216 (1.235-8.374) and p-value 0.03.ConclusionAmong the ossicles, there is a relationship between the stapes erosion and the facial canal dehiscence in chronic otitis squamous. Erosion of ossicular chain especially stapes should alert surgeons towards the possibility of facial canal dehiscence.